2018
DOI: 10.1002/ejoc.201800388
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Based Chiral Amines via Aza‐Michael Additions to (–)‐Levoglucosenone Under Aqueous Conditions

Abstract: Chiral amines are highly coveted within the fine‐chemical industry and sustainable synthetic methodologies for their production are of great value. By harnessing the chirality present in cellulose‐derived (–)‐levoglucosenone (LGO), several bio‐based sp3‐rich amines containing up to four chiral centres have been readily prepared under aqueous conditions without using any catalysts, ligands, auxiliaries or resolutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…LGO is not yet cheaply available, while studies are ongoing for the development of more economical production processes like that of our previous study, which demonstrated the possibility of solvent free LGO production by reforming of volatiles from cellulose pyrolysis over a packed bed catalyst. Because of its highly functionalized structure, LGO has been used for synthesis of many natural and synthetic compounds as the platform, but the application has been limited mainly to those specialty chemicals. Recent studies have opened up new ways to reach chemicals with potential heavy demand, e.g., polyols, Cyrene (green solvent), and, notably, HMF/LA. , The formation of furanic compounds from LGO with substantial yields was identified in the catalytic pyrolysis of cellulose in sulfolane with sulfuric acid about ten years ago, and a recent series of works , by Huber’s group demonstrated selective production of HMF and LA with cellulose conversion via LGO in a mixture of tetrahydrofuran and water containing sulfuric acid as catalyst. The reaction system is clearly superior to using glucose as intermediate or feedstock in terms of chemicals required for the conversion and the product yield, but it is not yet an economically viable and green production process.…”
Section: Introductionmentioning
confidence: 99%
“…LGO is not yet cheaply available, while studies are ongoing for the development of more economical production processes like that of our previous study, which demonstrated the possibility of solvent free LGO production by reforming of volatiles from cellulose pyrolysis over a packed bed catalyst. Because of its highly functionalized structure, LGO has been used for synthesis of many natural and synthetic compounds as the platform, but the application has been limited mainly to those specialty chemicals. Recent studies have opened up new ways to reach chemicals with potential heavy demand, e.g., polyols, Cyrene (green solvent), and, notably, HMF/LA. , The formation of furanic compounds from LGO with substantial yields was identified in the catalytic pyrolysis of cellulose in sulfolane with sulfuric acid about ten years ago, and a recent series of works , by Huber’s group demonstrated selective production of HMF and LA with cellulose conversion via LGO in a mixture of tetrahydrofuran and water containing sulfuric acid as catalyst. The reaction system is clearly superior to using glucose as intermediate or feedstock in terms of chemicals required for the conversion and the product yield, but it is not yet an economically viable and green production process.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Greatrex and coworkers [ 10 ] reported the aza-Michael conjugate addition to levoglucosenone under aqueous conditions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the absence of any chiral catalyst, cellulose-derived (−)-levoglucosenone can undergo well-controlled reactions like 1,3-dipolar cycloaddition, aza-Michael addition or isomerization, being enantioselectively converted into polysub-stituted pyrrolidines or 1,2,3-triazoles. [327][328][329] A versatile protocol via multicomponent Ugi-type reactions of unprotected saccharides and L-or D-configured amino acids is accessible to 1,2-syn or anti configured products, respectively. 330 In this regard, the exploitation of synthetic protocols to biomassderived chiral molecules, especially those with potent bioactivities, is promising with respect to green manufacturing processes.…”
Section: N-heterocycles With Controllable Ring Size/typementioning
confidence: 99%